2014
DOI: 10.1080/10548408.2014.883949
|View full text |Cite
|
Sign up to set email alerts
|

Destination Online Communication: Why Less is Sometimes More. A Study of Online Communications of English Destinations

Abstract: This research investigates the relationship between website design and the website end--user experience of a vast number of English tourism destinations, both local and regional ones. Following recent research in the field, this paper evaluates destinations' online communication, based on the implemented website features and on the effectiveness of the communication itself, borrowing its research methodology from different domains. After content and functionality analysis, a user--experience, scenario--based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…DMOs have to face the ICT challenges and adapt their strategies (Gretzel, Fesenmaier, Formica, and O'Leary, 2006;Hays, Page, & Buhalis, 2013). DMOs have to address these strategies in an increasingly competitive global environment with more sophisticated consumers, and with growing needs for greater efficiency and customer satisfaction (Buhalis, 2000;Inversini, Cantoni, & De Pietro, 2014;Law et al, 2014). DMOs can take advantage of the internet to customize the information they provide and interact directly with tourists (Buhalis & Law, 2008;Pan & Fesenmaier, 2006;Pike & Page, 2014) who, in turn, are increasingly using DMO websites and social media as sources of information (Hays et al, 2013;Law, Qi, & Buhalis, 2010;Luna-Nevarez & Hyman, 2012;Mariani, Di Felice, & Mura, 2016;Woodside, Ramos-Mir, & Duque, 2011;Xiang & Gretzel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…DMOs have to face the ICT challenges and adapt their strategies (Gretzel, Fesenmaier, Formica, and O'Leary, 2006;Hays, Page, & Buhalis, 2013). DMOs have to address these strategies in an increasingly competitive global environment with more sophisticated consumers, and with growing needs for greater efficiency and customer satisfaction (Buhalis, 2000;Inversini, Cantoni, & De Pietro, 2014;Law et al, 2014). DMOs can take advantage of the internet to customize the information they provide and interact directly with tourists (Buhalis & Law, 2008;Pan & Fesenmaier, 2006;Pike & Page, 2014) who, in turn, are increasingly using DMO websites and social media as sources of information (Hays et al, 2013;Law, Qi, & Buhalis, 2010;Luna-Nevarez & Hyman, 2012;Mariani, Di Felice, & Mura, 2016;Woodside, Ramos-Mir, & Duque, 2011;Xiang & Gretzel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, these studies illustrate the heightened use made by the tourism sector of communication technologies (Inversini;De-Pietro, 2014), although it has also been demonstrated that the pace at which DMOs adapt to changes is highly varied (Gretzel;Fesenmaier, 2004;Fernández-Cavia et al, 2017).…”
Section: Review Of Literaturementioning
confidence: 83%
“…This factor is critical, because customers use e-tourism websites as information sources. Therefore, they need to be designed to match end users' needs and expectations [67]. Lists of information about a product or destination are not effective in helping tourists plan their trips [43].…”
Section: User Preferencesmentioning
confidence: 99%